Instructing with advanced collaboration technology: lessons learned and unexpected transformations - Nosek, John T. (2006)
This paper provides lessons learned and some unexpected transformations in the learning process when advanced collaboration technology was used to overcome limitations of a popular, existing collaboration technology. The activities pursued in these advanced undergraduate and graduate computer and information sciences courses replicate many of the activities in collaborative knowledge work in organizations. Therefore, the lessons learned should be applicable to transforming other kinds of joint knowledge work in general.